Robustaflavone promotes osteogenic potential and bone regeneration of dental pulp stem cells by modulating mitochondrial activity and smad-independent signaling - Hyung-Mun Yun; Yoon Ju Kwon; Soo Hyun Kim; Kyung-Ran Park (Tissue and Cell, 2026)

Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Suppressing microRNA396 activity enhances regeneration efficiency of viable shoots from cotyledon explants in pepper - Min Jun Shin; Seong Sub Ku; Su-Jin Park; Sang Un Park; Sung Ran Min; Hyun-Soon Kim; Hyo-Jun Lee (Plant Biotechnology Reports, 2026)

Mitogenomic Characterization and Phylogenetic Insights of the Ornamental Sail-Fin Molly (Poecilia velifera) in Non-Native Indonesian Waters - Sarifah Aini; Rina; Sinar Pagi Sektiana; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Muhammad Hilman Fu’adil Amin; Won-Kyo Jung; Angkasa Putra; I Nyoman Suyasa; Shantanu Kundu; Hyun-Woo Kim (Biochemical Genetics, 2026)

Development of polymorphic simple sequence repeat markers for assessing genetic diversity and cross-species transferability in Polygonatum species - Raveendar Sebastin; Ki Hyun Kim; Hye Ran Shin; Yumi Kim; Sewon Oh; Ick Hyun Jo; Ju-Kyung Yu; Yi Lee; Yoon-Sup So; Jong-Wook Chung (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Effect of pesticide formulation on initial residue levels in crops: a meta-analysis approach - So-Hee Kim; Hye-Ran Eun; Min-Seok Kim; Hyun-Woo Kim; Ji Won Lee; Hyun Ho Noh (Environmental Pollution, 2025)

Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

Quinine inhibits myogenic differentiation by disrupting AKT signaling pathway - Mi Ran Byun; Sou Hyun Kim; RanJu Woo; Seung Jun Noh; Sang Hoon Joo; Young-Suk Jung; Joon-Seok Choi (Toxicological Research, 2025)

Nitric acid modified powdered activated carbon for simultaneous adsorption of lead and phenol in aqueous solution - Hyun-Kyung Kim; So-Jeong Kim; Hye-Ran Kim; Jae-Woo Park (Journal of Environmental Chemical Engineering, 2024)

Association between TGF-β/BMP signaling pathway polymorphisms and the risk of primary ovarian insufficiency in Korean women - Yong Hyun Ha; Ji Hyang Kim; Chang Soo Ryu; Ji Won Kim; Eun Ju Ko; Jeong Yong Lee; Ji Eun Shin; Young Ran Kim; Eun Hee Ahn; Nam Keun Kim (Genes & Genomics, 2024)

Hydroprocessing characteristics of palm fatty acid distillate in palm oil into low-carbon biofuel - Soo Hyun Kim; Hyerim Ko; Mi Ran Lee; Jin-Kuk Kim; Young-Woong Suh (Fuel, 2024)

Integrative Taxonomy Clarifies the Historical Flaws in the Systematics and Distributions of Two Osteobrama Fishes (Cypriniformes: Cyprinidae) in India - Boni Amin Laskar; Dhriti Banerjee; Sangdeok Chung; Hyun-Woo Kim; Ah Ran Kim; Shantanu Kundu (Fishes, 2024)
The taxonomy and geographical distributions of Osteobrama species have historically posed challenges to ichthyologists, leading to uncertainties regarding their native ranges. While traditional taxonomy has proven valuable in classification, the utility of an integrated approach is restricted for this particular group due to limitations in combining information from biogeography, morphology, and genetic data. This study addresses the taxonomic puzzle arising from the recent identification of Osteobrama tikarpadaensis in the Mahanadi and Godavari Rivers, casting doubt on the actual distribution and systematics of both O. tikarpadaensis and Osteobrama vigorsii. The research reveals distinctions among specimens resembling O. vigorsii from the Krishna and Godavari riverine systems. Notably, specimens identified as O. vigorsii from the Indian Museum exhibit two pairs of barbels, while those from the Godavari River in this study are identified as O. tikarpadaensis. Inter-species genetic divergence and maximum likelihood phylogeny provide clear delineation between O. vigorsii and O. tikarpadaensis. The study suggests that O. vigorsii may be limited to the Krishna River system in southern India, while O. tikarpadaensis could potentially extend from the Mahanadi River in central India to the Godavari River in southern India. Proposed revision to morphological features for both species, accompanied by revised taxonomic keys, aim to facilitate accurate differentiation among Osteobrama congeners. The data generated by this research provide a resource for future systematic investigations into cyprinids in India and surrounding regions. Further, the genetic diversity information obtained from various riverine systems for Osteobrama species will be instrumental in guiding aquaculture practices and formulating effective conservation action plans.

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Flexural properties of ultra-high performance fiber reinforced concrete based on three-dimensional random distribution of steel fibers - Ya Lu; Jingcheng Han; Puyan Wang; Xiangguo Wu; Hyeon-Jong Hwang; Jian Zhou; Ran Li; Sung-Hyun Kim; Ho-Jun Lee (Engineering Structures, 2023)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Establishment of a qualified ex vitro-acclimatized whole plant reproduction system using secondary somatic embryos in Panax ginseng - Ju Hee Kim; Mi Young Kim; Jae Hyun Lee; Jang Uk Kim; Ok Ran Lee (Plant Biotechnology Reports, 2023)

First Mitogenome of Endangered Enteromius thysi (Actinopterygii: Cypriniformes: Cyprinidae) from Africa: Characterization and Phylogeny - Shantanu Kundu; Jerome D. Binarao; Piyumi S. De Alwis; Ah Ran Kim; Soo-Rin Lee; Sapto Andriyono; Fantong Zealous Gietbong; Hyun-Woo Kim (Fishes, 2022)
The complete mitochondrial genome of endangered Enteromius thysi was determined from Cameroon in Western Africa. The genome was 16,688 bp in length, comprising 37 genes (13 PCGs, 2 rRNAs, 22 tRNAs, and an AT-rich control region). The heavy strand accommodates 28 genes (12 PCGs, 2 rRNAs, and 14 tRNAs), whereas the light strand holds 9 genes (NAD6 and 8 tRNAs). The E. thysi mitogenome is AT-biased (60.5%), as exhibited in other Enteromius species. Most of the PCGs start with the ATG initiation codon, except COI, with GTG, and seven PCGs end with the TAA termination codon, except some with an incomplete termination codon. Most of the tRNAs showed classical cloverleaf secondary structures, except tRNA-serine (trnS1). Bayesian phylogeny distinctly separated E. thysi from other congeners. The control regions of Enteromius species exhibited highly variable nucleotides, and parsimony-informative sites were found in the conserved sequence block-III (CSB-III) compared with other domains and a unique 9 bp tandem repeat (ATGCATGGT) in the variable-number tandem repeats (VNTRs) region of E. thysi. The present phylogeny with limited mitogenomes showed an uneven diversity and evolutionary patterns of Enteromius species distributed in the northwestern and southeastern riverine systems in Africa, which warrants further investigation. Based on the results of the present study, we recommend additional surveys, in-depth taxonomy, and the generation of more mitogenomes that could resolve the diversification pattern of Enteromius species in Africa.

Retraction Note: Fluoxetine induces apoptosis through endoplasmic reticulum stress via mitogen-activated protein kinase activation and histone hyperacetylation in SK-N-BE(2)-M17 human neuroblastoma cells - Ji Hyun Choi; Yeon Ju Jeong; Ah-Ran Yu; Kyung-Sik Yoon; Wonchae Choe; Joohun Ha; Sung Soo Kim; Eui-Ju Yeo; Insug Kang (Apoptosis, 2022)

Correction to: A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2022)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

A single amino acid insertion in LCYB2 deflects carotenoid biosynthesis in red carrot - Seung Hee Jo; Hyun Ji Park; Areum Lee; Haemyeong Jung; Sung Ran Min; Hyo-Jun Lee; Hyun-Soon Kim; Min Jung; Ji Young Hyun; Youn-Sung Kim; Hye Sun Cho (Plant Cell Reports, 2021)

Metabarcoding Analysis of Ichthyoplankton in the East/Japan Sea Using the Novel Fish-Specific Universal Primer Set - Ah Ran Kim; Tae-Ho Yoon; Chung Il Lee; Chang-Keun Kang; Hyun-Woo Kim (Frontiers in Marine Science, 2021)
The spatiotemporal distribution of fish larvae and eggs is fundamental for their reproduction and recruitment in aquatic ecosystems. Here, a metabarcoding strategy was employed as an alternative to a conventional ichthyoplankton survey, which requires a considerable amount of time, labor, and cost. First, a piscine-specific universal primer set (FishU) was designed to amplify the region, flanking the highly conserved mitochondrial 12S and 16S ribosomal genes, and it was optimized for the MiSeq platform. Based on both in silico and in vitro analyses, the newly designed FishU primers outperformed the two previously reported fish-specific universal primer sets (ecoPrimer and MiFish) in taxon coverage, specificity, and accuracy in species identification. The metabarcoding results by FishU primers successfully presented the diversity of ichthyoplankton directly from the zooplankton net samples in the East/Japan Sea, presenting more accurate and plentiful species numbers than those by MiFish primers. Thus, the metabarcoding analysis of ichtyoplankton using the newly designed FishU primers is a promising tool for obtaining useful data to understand the reproduction of fish, such as spawning sites, reproductive periods, population structures, feeding ecology, and diet.

Action mechanism of anti-wrinkle effect of Rhamnus yoshinoi methanol extract in human dermal fibroblast and keratinocyte cell lines - Hyun Ok Kim; Kyoung Ran Shin; Byeong-Churl Jang; Young Chul Kim (Toxicological Research, 2020)

The complete genome sequence of apple rootstock virus A, a novel nucleorhabdovirus identified in apple rootstocks - Dasom Baek; Seungmo Lim; Ho-Jong Ju; Hyun-Ran Kim; Su-Heon Lee; Jae Sun Moon (Archives of Virology, 2019)

Perinatal exposure to di-ethyl-hexyl phthalate via parenteral route induced polycystic ovarian syndrome-like genetic and pathologic changes in F1 offspring mice - Ki Hyun Kil; Mee Ran Kim; Jang Heub Kim; Hyun Hee Cho (Molecular & Cellular Toxicology, 2019)

Enhanced tolerance to heat stress in transgenic tomato seeds and seedlings overexpressing a trehalose-6-phosphate synthase/phosphatase fusion gene - Jae Il Lyu; Ji Hyun Park; Ju-Kon Kim; Chang-Hyu Bae; Won-Joong Jeong; Sung Ran Min; Jang R. Liu (Plant Biotechnology Reports, 2018)

Characterization of Human Fetal Cartilage Progenitor Cells During Long-Term Expansion in a Xeno-Free Medium - Hwal Ran Kim; Jiyoung Kim; So Ra Park; Byoung-Hyun Min; Byung Hyune Choi (Tissue Engineering and Regenerative Medicine, 2018)

Factors affecting the public awareness and behavior on antibiotic use - Kyungmin Huh; Doo Ryeon Chung; So Hyun Kim; Sun Young Cho; Young Eun Ha; Cheol-In Kang; Kyong Ran Peck; Jae-Hoon Song (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Hepatocyte SHP deficiency protects mice from acetaminophen-evoked liver injury in a JNK-signaling regulation and GADD45β-dependent manner - Yong-Hoon Kim; Jung-Ran Noh; Jung Hwan Hwang; Kyoung-Shim Kim; Dong-Hee Choi; Jae-Hoon Kim; Sung Je Moon; Ji Hyun Choi; Yann Hérault; Tae Geol Lee; Hueng-Sik Choi; Chul-Ho Lee (Archives of Toxicology, 2018)

RETRACTED ARTICLE: Fluoxetine induces apoptosis through endoplasmic reticulum stress via mitogen-activated protein kinase activation and histone hyperacetylation in SK-N-BE(2)-M17 human neuroblastoma cells - Ji Hyun Choi; Yeon Ju Jeong; Ah-Ran Yu; Kyung-Sik Yoon; Wonchae Choe; Joohun Ha; Sung Soo Kim; Eui-Ju Yeo; Insug Kang (Apoptosis, 2017)

Analysis of ovarian gene expression in F2 mouse following perinatal exposure to DEHP via the parenteral route - Ki Hyun Kil; Mee Ran Kim; Jang Heub Kim; Yeon Ji Jung; Hyun Hee Cho (Molecular & Cellular Toxicology, 2016)

Characterization of PyGUS gene silencing in the red macroalga, Pyropia yezoensis - Yoon Ju Shin; Jong-Min Lim; Ji Hyun Park; Dong-Woog Choi; Mi Sook Hwang; Eun-Jeong Park; Sung Ran Min; Suk Weon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2016)

Effects of zinc oxide nanoparticle dispersants on cytotoxicity and cellular uptake - Mi-Rae Jo; Hae-Eun Chung; Hyun-Jin Kim; Song-Hwa Bae; Mi-Ran Go; Jin Yu; Soo-Jin Choi (Molecular & Cellular Toxicology, 2016)

Fermented Saccharina japonica (Phaeophyta) improves neuritogenic activity and TMT-induced cognitive deficits in rats - Hyun-Jung Park; Mi-Sook Lee; Hyun Soo Shim; Gyeong-Ran Lee; Sun Yong Chung; Young Mi Kang; Bae-Jin Lee; Yong Bae Seo; Kyung Soo Kim; Insop Shim (Algae, 2016)

Complete genome sequence of a novel endornavirus isolated from hot pepper - Seungmo Lim; Kil Hyun Kim; Fumei Zhao; Ran Hee Yoo; Davaajargal Igori; Su-Heon Lee; Jae Sun Moon (Archives of Virology, 2015)

Transcriptomic study of mouse embryonic neural stem cell differentiation under ethanol treatment - Chanchal Mandal; Ji Hyun Park; Mi Ran Choi; Sun Hwa Kim; Abimbola Comfort Badejo; Jin Choul Chai; Young Seek Lee; Kyoung Hwa Jung; Young Gyu Chai (Molecular Biology Reports, 2015)

Genome sequence of a recombinant brassica yellows virus infecting Chinese cabbage - Seungmo Lim; Ran Hee Yoo; Davaajargal Igori; Fumei Zhao; Kil Hyun Kim; Jae Sun Moon (Archives of Virology, 2015)

Silk fibroin based hydrogel for regeneration of burn induced wounds - Hyung Woo Ju; Ok Joo Lee; Bo Mi Moon; Faheem A. Sheikh; Jung Min Lee; Jung-Ho Kim; Hyun Jung Park; Dong Wook Kim; Min Chae Lee; Soo Hyeon Kim; Chan Hum Park; Hae Ran Lee (Tissue Engineering and Regenerative Medicine, 2014)

Freezing and Frost Damage of Potato Plants: a Case Study on Growth Recovery, Yield Response, and Quality Changes - Dong Chil Chang; Hwang Bae Sohn; Ji Hong Cho; Ju Sung Im; Yong Ik Jin; Gyeong Ran Do; Su Jeong Kim; Hyun Mook Cho; Yong Beom Lee (Potato Research, 2014)

Thymol from Thymus quinquecostatus Celak. protects against tert-butyl hydroperoxide-induced oxidative stress in Chang cells - Yon-Suk Kim; Jin-Woo Hwang; Seo-Hee Kang; Ee-Hwa Kim; You-Jin Jeon; Jae-Hyun Jeong; Hye-Ran Kim; Sang-Ho Moon; Byong-Tae Jeon; Pyo-Jam Park (Journal of Natural Medicines, 2014)

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal inhibits tumor growth via suppression of NF-κB and induction of death receptor 6 - Jung Ok Ban; Young-Suk Jung; Dae Hwan Kim; Kyung-Ran Park; Hyung-Mun Yun; Nam Jin Lee; Hee Pom Lee; Jeong-Hyun Shim; Heon-Sang Jeong; Yun-Hee Lee; Young Wan Ham; Sang-Bae Han; et al. (Apoptosis, 2014)

Functional Analysis of Histone Demethylase Jmjd2b on Lipopolysaccharide-Treated Murine Neural Stem Cells (NSCs) - Nando Dulal Das; Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Hyung Tae Lee; Amitabh Das; Seung Hyun Kim; Young Gyu Chai (Neurotoxicity Research, 2013)

Identification of genes induced by Venturia nashicola in indigenous Korean pear ‘Hwangsilri’ - Il Sheob Shin; Kyung Mi Bae; Ga Young Nam; Byoung-Cheorl Kang; Jaean Chun; Kang Hee Cho; Se Hee Kim; Hyung Seok Choi; Hyun Ran Kim; Hae Sung Hwang; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2012)

Comparative analysis of pathogenesis-related protein 10 (PR10) genes between fungal resistant and susceptible peppers - Hyun Cheol Soh; Ae Ran Park; Sangkyu Park; Kyoungwhan Back; Jae Bok Yoon; Hyo Guen Park; Young Soon Kim (European Journal of Plant Pathology, 2012)

Gilvimarinus agarilyticus sp. nov., a new agar-degrading bacterium isolated from the seashore of Jeju Island - Byung-Chun Kim; Mi Na Kim; Kang Hyun Lee; Hyun Soon Kim; Sung Ran Min; Kee-Sun Shin (Antonie van Leeuwenhoek, 2011)

Development of gene-based markers for the Bs2 bacterial spot resistance gene for marker-assisted selection in pepper (Capsicum spp.) - Hai Thi Hong Truong; Ki-Taek Kim; Su Kim; Myoung-Cheol Cho; Hyun-Ran Kim; Jong-Gyu Woo (Horticulture, Environment, and Biotechnology, 2011)

High-level expression of a human β-site APP cleaving enzyme in transgenic tobacco chloroplasts and its immunogenicity in mice - Jung Won Youm; Jae Heung Jeon; Hee Kim; Sung Ran Min; Mi Sun Kim; Hyouk Joung; Won Joong Jeong; Hyun Soon Kim (Transgenic Research, 2010)

Comparative studies of skeletal muscle proteome and transcriptome profilings between pig breeds - Nam-Kuk Kim; Hye-Ran Park; Hwi-Cheul Lee; Duhak Yoon; Eun-Suk Son; Yeun-Song Kim; Se-Ra Kim; Oun-Hyun Kim; Chang-Soo Lee (Mammalian Genome, 2010)

The development of herbicide-resistant maize: stable Agrobacterium-mediated transformation of maize using explants of type II embryogenic calli - Hyun A. Kim; Setyo Dwi Utomo; Suk Yoon Kwon; Sung Ran Min; Jin Seog Kim; Han Sang Yoo; Pil Son Choi (Plant Biotechnology Reports, 2009)

Characterization of a mannose-6-phosphate isomerase from Geobacillus thermodenitrificans that converts monosaccharides - Soo-Jin Yeom; Nam-Hee Kim; Ran-Young Yoon; Hyun-Jung Kwon; Chang-Su Park; Deok-Kun Oh (Biotechnology Letters, 2009)

The complete chloroplast genome sequences of Solanum tuberosum and comparative analysis with Solanaceae species identified the presence of a 241-bp deletion in cultivated potato chloroplast DNA sequence - Hwa-Jee Chung; Jong Duk Jung; Hyun-Woo Park; Joo-Hwan Kim; Hyun Wook Cha; Sung Ran Min; Won-Joong Jeong; Jang Ryol Liu (Plant Cell Reports, 2006)

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins - Min Jung Kim; Byung-Kook Ham; Hwa Ran Kim; In-Ju Lee; Young Jin Kim; Ki Hyun Ryu; Young In Park; Kyung-Hee Paek (Plant Molecular Biology, 2005)

Anti-fungal effects of phenolic amides isolated from the root bark of Lycium chinense - Dong Gun Lee; Yoonkyung Park; Mi-Ran Kim; Hyun Jun Jung; Young Bae Seu; Kyung-Soo Hahm; Eun-Rhan Woo (Biotechnology Letters, 2004)

CHRK1, a chitinase-related receptor-like kinase, plays a role in plant development and cytokinin homeostasis in tobacco - Jeong Hee Lee; Kentaro Takei; Hitoshi Sakakibara; Hye Sun Cho; Do Myung Kim; Youn Sung Kim; Sung Ran Min; Woo Taek Kim; Dae Young Sohn; Yong Pyo Lim; Hyun-Sook Pai (Plant Molecular Biology, 2003)